Feasibility Study for the Installation of Wind Energy Conversion Systems in Pakistan - Saif ur Rehman,; Muhammad Shoaib,; Shamim Khan ,; Muhammad Jahangir, (Journal of Basic & Applied Sciences, 2016)
Wind generated electricity is one of the most attractive methods of electric power generation in a third world country like Pakistan. This paper presents the economic and technical viability of wind energy generation in remote and rural areas of Sindh (Pakistan). In light of this, Three wind turbines with power ratings of 660 kW, 1,000 kW and 18,00 kW are chosen. The economic analysis has been carried out by four economic indexes that are: cost benefit analysis (CBI), Net Present Value (NPV), Pay Back Period (PBP) and the Costof Energy (COE $/kWh). The wind speed data for this study was obtained from the Pakistan meteorological | department, measured at heights of 10m and 30 m, that span from 2002 to 2005.The outcome of the study showed that, the highest annual average energy of 5396 MWh/yr could be generated by Vestas V80 (with power capacity of 1.8 MW). Furthermore, the baseline economic evaluation of all the selected turbines, indicted that V80-1.8 MW gave the least cost (0.043 $/KWh) of electricity production at 80m hub height while the Sensitivity of the selected parameters showed that NPV is more sensitive to retail price of local electricity cost.